Pengaruh teknik sosiodrama dalam bimbingan kelompok terhadap peningkatan perilaku prososial Siswa - Nurhidaya, Siti (Universitas Negeri Makassar, 2017)
The objectives of the research are to discover (1) the description of the implementation of socio-drama , (2) the description of the students’ pro-social behaviors before and after the implementation of socio-drama technique in group guidance, (3) wether there is influence of socio-drama technique in group guidance toward the improvementof pro-social behaviors of the students. The research employed quantitative approach by using true experimental desugn in form of pretest posttest control group design. The subjects of the research were 30 students of class XI who were identified had low pro-social behaviors divided into 15 students in the experiment group and 15 students in the control group. The data collection techniques employed pro-social scale and observation. The results of the reaseacrh reveal that (1) Socio-drama technique in group guidance was implemented in four sessions; first session builds the sense of helping each other, second session builds cooperation attitude, third session builds the senseof honesty, and fourth sessions builds students’ emphaty, (2) the level of pro-social behaviors of the students at before treatment was given to the experiment and control group in this case socio-drama training in group guidance is in low category, but after treatment was given, the level of students’ pro-social behaviors in experiment group improve or in high category; whereas, students in control group are still in low category, (3) the implementation of socio-drama technique in group guidance gives positive influence significantly towards the improvement of the students pro-social behaviors, meaning that when socio-drama technique in group guidance is implemented, it helps improving pro-social behaviors of the students.